Cytotoxicity of active ingredients extracted from plants of the Brazilian Cerrado - Soares, Veronica C.G.; Bonacorsi, Cibele [UNESP]; Andrela, Alana L.B.; Bortoloti, Lígia V.; De Campos, Stepheny C.; Fagundes, Fábio H.R.; Piovani, Márcio; Cotrim, Camila A.; Vilegas, Wagner [UNESP]; Toyama, Marcos H. [UNESP] (SAGE Publications, 2011)
Cytotoxicity assays are needed for the screening of natural products with potential anti-inflammatory. The purpose of this study was to compare the basal cytotoxicity of active ingredients extracted from plants of the Brazilian cerrado. The viability was assayed with the neutral red uptake assay in Mac Coy cells after 24h of exposition. The dose evaluated was 50 μg/μL. The test substances were: cinnamic acid, p-coumaric acid, chlorogenic acid, syringic acid, vannilic acid, homogentisic acid, scandenin, palustric acid, diosgenin, cabraleone. Studies of cytotoxicity demonstrated that all active compounds evaluated have low toxicity in vitro. The substances showed cell viability above 60% for the concentration used. However, the cinnamic acid, sacandenin and palustric acid showed highest toxicity with a 50% reduction in cell viability for the dose of 50 μg/μL. Cytotoxic screening results are useful to estimate the best concentrations of those compounds with potential anti-inflammatory without their cause cell death.
Keywords: Brazilian cerrado; Cytotoxicity; Natural products